"An understanding, a way of life": An exploration of learning disability professionals' experiences of compassion. (13th January 2020) - Brennan, Hope; Westbrook, Jenna; Parry, Sarah
Accessible summary: Compassion is described as a sensitivity to suffering in oneself and others, with an intent to alleviate and prevent it (Gilbert, Advances in Psychiatric Treatment, 2009, 15, 199). A population within health care that has limited research on compassionate care is that of learning disabilities. The current study aimed to explore the experiences of compassion of professionals within learning disability services. Attention was given to the flow of compassion between professionals and service users, as well as the growth of compassion, over time. The findings suggested that compassion is difficult to foster in learning disability services that also value time‐pressured, target‐driven outputs. More needs to be done to support services to encourage compassion in care, for example by considering candidates' compassion at recruitment and through supportive supervision and group reflection, for both people with learning disabilities and the healthcare professionals employed. Abstract: Background: Compassion is one of the six core principles that the NHS means to promote within health care. Research concerning compassion within learning disability services is scarce; therefore, the current study aimed to explore the experiences of compassion of professionals within learning disability services. Materials and Methods: Twelve professionals from learning disability services completed a quantitative measure of professional quality of life and answered a series of qualitative questions regarding their experiences of compassion, in either an online survey or interview. Results: Narrative analysis was used to interpret participants' experiences of compassion. Three chapters were generated based on thematic and linguistic connections. In chapter 1, participants explored their compassionate identities. In chapter 2, participants detailed the flow of compassion, experienced interpersonally and intrapersonally. In chapter 3, participants described their compassionate growth, owing to significant life events over time. Conclusions: Recommendations for improving compassionate care have been made, including encouraging self‐compassion for professionals through training screening for compassion during recruitment and including people with learning disabilities on interview panels.